“Analisis Makna Semantik Pada Puisi Chairil Anwar DOA” - Putri Firmawindy Turnip; Alzyra Fatihah Simatupang; Elsah Sinurat; Yuliana Sari (CV. Alim's Publishing, 2024)
This study analyzes the semantic meaning in the poem